SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PRIORITAS PERBAIKAN GANGGUAN JARINGAN FTTH PADA CV. PERDANA MITRA INOVASI MENGGUNAKAN METODE TOPSIS BERBASIS WEB - Slamet Wirawan; I Gusti Lanang Eka Prismana; Ahmad Heru Mujianto; Tanhella Zein Vitadiar (Fakultas Teknologi Informasi, 2024)
Information technology has become a crucial element in various fields, including services in Indonesia,which continue to develop rapidly. The use of information technology allows companies to accessinformation quickly, accurately, and precisely, as well as provide effective and efficient services. CV PerdanaMitra Inovasi, a local internet service provider in Rejoagung Village, Jombang Regency, faces challenges inthe conventional and slow customer complaint reporting process. With thousands of customers and a limitednumber of admins, prioritizing issues is difficult.In order to solve this issue, a decision support system (DSS) based on the TOPSIS technique was created toassist in establishing the importance of fixing FTTH network issues.. This system allows for the selection ofissues that should be addressed first and provides a list of repair solutions. The TOPSIS method was chosenbecause it can combine quantitative and qualitative elements accurately and precisely. The criteria in thecalculation include the number of affected customers, the number of technicians required, repair costs,estimated repair time, and distance. It is anticipated that using this method, the decision-making process inhandling FTTH network issues will be faster and easier, resulting in more optimal customer service.